Gender Representation in Religious Sermons: A Critical Language Study of Popular Indonesian Preachers on YouTube - M. Isnaini; Winarsih, Anis Dwi; Yustisia, Karlina Karadila (KOMUNITAS, 2025)
The gender representations conveyed through the language of religious speakers play a significant role in shaping public perceptions of the roles of men and women. This study examines sermons delivered by two popular figures, Ustadz Abdul Somad and Ustadzah Oki Setiana Dewi, to explore how gender constructions are represented through lexical choices, speech styles, and discourse structures. Using a critical language study approach, the findings reveal that although both speakers convey religious messages with different styles, Ustadz Abdul Somad tends to be normative and direct, while Ustadzah Oki adopts a more narrative and emotional approach, both still reproduce traditional gender patterns. Women are often associated with obedience, domesticity, and gentleness, whereas men are portrayed as leaders, protectors, and holders of authority. These findings demonstrate that the language used in religious sermons not only communicates moral and spiritual messages but also contributes to reinforcing social constructions of gender inequality.